A circuit board conformal coating material for high frequency fields and a preparation method thereof

By using a combination of modified epoxy resin, polyfluorocarbon and modified silica in the conformal materials in the high frequency field, the problems of high dielectric loss and poor mechanical properties in the prior art are solved, and low mediation is achieved Material with stable electrical loss and mechanical properties, suitable for flexible circuit boards with 5G high-frequency technology.

CN116179023BActive Publication Date: 2025-01-10YIK SHING TAT (SHENZHEN) NEW MATERIAL CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202310131298.9
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-02-17
Publication Date
2025-01-10
Estimated Expiration
2043-02-17

AI Technical Summary

Technical Problem

In the high-frequency field, existing conformal materials cannot meet the requirements of 5G products for low dielectric loss, stable mechanical performance and protective film density, and are also very costly and difficult to take into account both mechanical strength and stability during production.

Method used

Using specific combinations of polymers, fillers and modifiers, including modified epoxy resins, polyfluorocarbons, vinyl polymers and porous/nano-scale silica, the stability of fillers is enhanced by modifier treatment and Adhesive properties of the material, optimize the resin group content to reduce dielectric loss and improve the density of the material.

Benefits of technology

It has achieved a dielectric constant between 2.2-2.5 and a loss factor between 0.0007. It is suitable for high-frequency fields, showing excellent adhesion, density, salt spray resistance, moisture and heat resistance and heat shock resistance. It is suitable for 5G high-frequency technology flexible circuit board.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004083972420000051
    Figure BDA0004083972420000051
  • Figure BDA0004083972420000131
    Figure BDA0004083972420000131
Patent Text Reader

Abstract

The present application provides a circuit board conformal coating material for high-frequency fields. The raw materials of the material include: by weight, 60-100 parts of polymer, 18-25 parts of filler, 0.1-3 parts of antioxidant, and 1-5 parts of flame retardant. By optimizing the polymer system and further specifying the group content and physical properties of the resin, the overall polarity and dielectric loss of the conformal material are reduced. The dielectric constant of the material is 2.2-2.5, and the loss factor is about 0.0007, which far exceeds the use requirement level of high-frequency materials and is more suitable for circuit materials under high frequency.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of conformal materials, H05K, and in particular to a conformal coating material for a circuit board used in a high-frequency field and a preparation method thereof. Background Art

[0002] With the popularization and development of 5G communication technology, people have higher and higher requirements for the characteristics of electronic products, such as high-speed signal transmission, high-precision control, signal stability, etc., especially under high-frequency and high-humidity conditions, requiring them to have stable dielectric properties, low dielectric constants and loss factors to improve the reliability of micro products. In the SMT process, conformal coating materials can form a dense film on the surface of the circuit board to protect the circuit board from the influence of moisture, high temperature, dust, salt spray, corrosive gas and other environments. The existing technology requires it to have good dielectric properties, dimensional stability at high temperatures, sufficient mechanical strength and toughness, etc. However, the film-forming materials used in conformal materials, such as epoxy compounds, polyurethanes, and silicone compounds, usually have a dielectric constant of about 3.5 and a loss factor of about 0.03, which is far from the requirement of the loss factor of less than 0.006 specified by 5G high-frequency products; polytetrafluoroethylene has low dielectric loss, but a high melting point, high sintering energy consumption, and high cost; and for some materials that can meet the dielectric loss, they cannot meet the needs of mechanical strength and stability during the production process.

[0003] Chinese patent CN115075057A discloses a low dielectric loss non-woven fabric and its preparation method and application. Its technology uses non-woven fabric and fluorine-containing resin emulsion with low dielectric loss, and effectively increases the content of dielectric filler. When its non-woven fabric is used for high-frequency copper-clad laminates, it shows low dielectric loss and high peel strength. However, the thermal expansion coefficient of the fluorine-containing resin emulsion used in its technology is relatively high, and its mechanical properties and dimensional stability are poor, which is not suitable for practical popularization and application. Chinese patent CN113978061A discloses a preparation method of low dielectric constant, low dielectric loss, and low CTE copper-clad laminates. Its technology uses mixed components such as special epoxy resin, SMA resin, benzoxazine resin, and cross-linking curing agent to prepare low-loss high-frequency copper-clad laminates, but its dielectric loss is about 0.006, which is at the edge of the specified value and cannot meet the application of higher-frequency working fields. There is still a large room for reducing its dielectric loss.

[0004] Therefore, it is necessary to develop a circuit board conformal coating material with low dielectric loss, stable mechanical properties, and high protective film density to meet the requirements of the 5G high-frequency field. Summary of the invention

[0005] In order to solve the above technical problems, the present invention first provides a circuit board conformal coating material for high-frequency fields. The raw materials of the material include: by weight, 60-100 parts of polymer, 18-25 parts of filler, 0.1-3 parts of antioxidant, and 1-5 parts of flame retardant.

[0006] Furthermore, the polymer includes but is not limited to at least two of epoxy resin or modified epoxy resin, polyimide, polyfluorocarbon compound, polyolefin, polyphenylene ether resin, polyisocyanate, and polyetheretherketone compound.

[0007] In one embodiment, the polymer comprises a modified epoxy resin.

[0008] Furthermore, the modified epoxy resin includes but is not limited to at least one of polyether-modified, polyphenylene ether-modified, cyanate-modified, polysiloxane-modified, nitrile rubber-modified, polycarbonate-modified, polyimide-modified, and phenol-phenolic modified epoxy resins.

[0009] Preferably, the modified epoxy resin includes at least one of polyphenylene ether modified epoxy resin, nitrile rubber modified epoxy resin, and phenol novolac modified epoxy resin.

[0010] Furthermore, the epoxy equivalent of the modified epoxy resin is 170-210 g / mol.

[0011] Furthermore, the polymer includes polyfluorocarbon.

[0012] Furthermore, the polyfluorocarbon compound includes but is not limited to at least one of polytetrafluoroethylene, poly(vinylidene fluoride), polyperfluoroethylene propylene, tetrafluoroethylene-perfluorovinyl ether copolymer, perfluoroalkoxy, ethylene-tetrafluoroethylene copolymer, and polyethylene chlorotrifluoroethylene.

[0013] Preferably, the polyfluorocarbon compound is selected from at least one of polytetrafluoroethylene, polyperfluoroethylene propylene, and tetrafluoroethylene-perfluorovinyl ether copolymer.

[0014] In a preferred embodiment, the polyfluorocarbon compound is polytetrafluoroethylene, and the solid content of the emulsion is 50-70%.

[0015] Furthermore, the polyolefin includes but is not limited to at least one of vinyl polymer, polypropylene, polyisobutylene, polystyrene, ethylene-octene copolymer, and ethylene-propylene-pentadiene polymer.

[0016] In one embodiment, the polyolefin comprises vinyl polymer and polypropylene.

[0017] Furthermore, the vinyl polymer is selected from any one or a combination of ethylene-vinyl acetate copolymer, ethylene-acrylate copolymer, butylene-ethylene-styrene copolymer, ethylene-ethylene oxide copolymer, ethylene-propylene copolymer, etc.

[0018] Preferably, the vinyl polymer is ethylene-vinyl acetate copolymer.

[0019] Furthermore, in the ethylene-vinyl acetate copolymer, the mass fraction of vinyl acetate (ie, VA) is 20-80%, and the melt index is 3-150 g / 10 min.

[0020] Furthermore, the VA content of the ethylene-vinyl acetate copolymer is 25-50%, and the melt index at 190°C / 2.16kg is 3-80g / 10min.

[0021] In a preferred embodiment, the ethylene-vinyl acetate copolymer has a VA content of 25-35% and a melt index of 7-65 g / 10 min at 190° C. / 2.16 kg.

[0022] Furthermore, the number average molecular weight of the polypropylene is 2000-10000, preferably 4000-8000, more preferably 4000-6000.

[0023] Furthermore, the polyisocyanate is selected from at least one of aliphatic polyisocyanates, cycloaliphatic polyisocyanates, and aromatic polyisocyanates, including but not limited to at least one of poly(triallyl isocyanurate), poly(triallyl cyanurate), poly(1,5-naphthyl diisocyanate), poly(4,4′-diphenylmethane diisocyanate), and poly(3,3′-dimethyl-4,4′-biphenyl diisocyanate).

[0024] Furthermore, the filler includes but is not limited to at least one of silica, quartz, beryllium oxide, alumina, magnesium oxide, mica, talc, nanoclay, aluminosilicate, magnesium oxide, magnesium hydroxide, aromatic polyamide fiber, boron nitride fiber, glass fiber or alkali-free glass fiber, and core-shell rubber particles.

[0025] In a preferred embodiment, the filler comprises silicon dioxide.

[0026] Furthermore, the silicon dioxide comprises porous silicon dioxide with a BET specific surface area of ​​220-280 m 2 / g, D50 particle size is 1-10μm.

[0027] In a preferred embodiment, the BET specific surface area of ​​the porous silica is 240-280 m 2 / g, D50 particle size is 1-4μm.

[0028] Furthermore, the filler also includes nano-scale silicon dioxide, and the average particle diameter is 10-50nm, preferably 15-30nm.

[0029] Furthermore, the mass ratio of the porous silica to the nano-sized silica is (3-4):(1-2).

[0030] Furthermore, the filler is modified by a modifier, and the modifier comprises the following structure:

[0031]

[0032] Wherein, R1, R2, R3, and R4 are selected from any one of substituted or unsubstituted C1-C15 straight-chain alkanes, branched alkanes, olefins, aromatic hydrocarbons, cycloalkanes, alkoxides, and silicon oxides; the substituted groups include but are not limited to at least one of hydroxyl, carboxyl, aldehyde, amino, halogen, cyano, thiol, and epoxy groups.

[0033] Furthermore, the substituted or unsubstituted C1-C15 straight-chain alkane includes but is not limited to at least one of methane, ethane, propane, butane, isopropane, pentane, hexane, heptane, octane, dodecane, aminopropane, hydroxypropane, and butanecarboxylic acid.

[0034] Furthermore, the substituted or unsubstituted C1-C15 aromatic hydrocarbon includes, but is not limited to, any one of 4-ethylphenylethylene, benzene, p-toluene, trifluorosubstituted benzene, biphenyl, p-aminobenzene, and phenol.

[0035] Furthermore, the substituted or unsubstituted C1-C15 cycloalkane includes but is not limited to any one of cyclopentane, cyclohexane, cyclooctane, cyclopentylpropene, cycloundecane, and hydroxymethyl-substituted cyclopentane.

[0036] Furthermore, the substituted or unsubstituted C1-C15 alkoxy compound includes but is not limited to at least one of methoxy, ethoxy, and chlorine-substituted methoxy.

[0037] Furthermore, at least one of R1, R2, R3, and R4 includes C1-C15 aromatic hydrocarbons.

[0038] Furthermore, the modifier may be a rigid structure, in which R1 includes C1-C15 aromatic hydrocarbons.

[0039] Furthermore, the modifier may also be a flexible structure, in which R1 includes a C1-C15 straight-chain alkane.

[0040] In a preferred embodiment, the modifier includes both a rigid structure and a flexible structure, and the mass ratio of the modifier whose R1 includes C1-C15 aromatic hydrocarbons to the modifier whose R1 includes C1-C15 straight-chain alkanes is (0.5-2):1. The present application modifies the filler so as to increase the mechanical strength of the system by the inorganic filler without adversely affecting the dielectric loss of the polymer material. As a powder, the inorganic filler has an interface effect with the polymer. This interface effect may cause film cracks on the conformal material, increase the dielectric loss of the material, and reduce its structural stability. The present application finds that when rigid and flexible structure modifiers are used to modify it at the same time, and the contents of the two and the types of other groups of the modifier are further specified, the filler modified by the modifier can exist stably in the organic system, and the crack propagation of the material is very low. Analysis shows that this is because the rigid and flexible structure modifiers produce specific intermolecular effects with other polymers or resins, which can maintain the system with good rigidity and toughness, make the material system have a suitable molecular activity volume, reduce the overall polarity and overall dielectric loss of the material, and enhance the adhesion and protection performance of the material to the circuit substrate.

[0041] Furthermore, the modification treatment method of the filler is: immersing the filler in a solution of 8-15wt% of the modifier, heating the system to 90-105°C, stirring the reaction for 4-8h, filtering and drying.

[0042] Furthermore, the antioxidant is at least one of a phosphorus antioxidant and a hindered phenol antioxidant.

[0043] Furthermore, the phosphorus-based antioxidant is at least one of triphenyl phosphite, diphenyl isooctyl phosphite, triisooctyl phosphite, triisodecyl phosphite, trilauryl phosphite, tritridecyl phosphite, pentaerythritol diisodecyl diphosphite, and poly(dipropylene glycol) phenyl phosphite.

[0044] Furthermore, the hindered phenol antioxidant is selected from any one of antioxidants 1010, 1076, 1098, and 1024.

[0045] Preferably, the antioxidant includes a phosphorus-based antioxidant and a hindered phenol antioxidant.

[0046] In a preferred embodiment, the antioxidant is tri(tridecyl) phosphite and antioxidant 1010, and the mass ratio is 1:(4-6).

[0047] Furthermore, the flame retardant is selected from at least one of bromine flame retardants, nitrogen flame retardants, phosphorus flame retardants, nitrogen-phosphorus flame retardants, and inorganic hydroxide flame retardants.

[0048] Furthermore, the flame retardant is selected from at least one of tetrabromobisphenol A, decabromodiphenyl ethane, decabromodiphenyl ether, triphenyl phosphate, resorcinol (diphenyl phosphate), ammonium pyrophosphate, ammonium polyphosphate, melamine polyphosphate, and melamine.

[0049] In a preferred embodiment, the flame retardant is decabromodiphenyl ether.

[0050] Secondly, the present application also provides a method for preparing the conformal coating material, comprising the following steps: putting the raw materials into a kneader, using a mold temperature controller to heat the heat transfer oil to 160-200°C, then evacuating to negative pressure, stirring and mixing for 2-3 hours, then returning to normal pressure, and continuing to stir for 0.5-1 hour; finally, loading the mixture into a mold and cooling it.

[0051] Furthermore, the coating of the conformal coating material on the PCB circuit board can be carried out in 1-2 steps, and the total dry film thickness is 100-200 μm.

[0052] Beneficial Effects

[0053] 1. This application optimizes the polymer system, further specifies the group content and physical parameters of the resin, and reduces the overall polarity and dielectric loss of the conformal material. The dielectric constant of the material is 2.2-2.5, and the loss factor is about 0.0007, which far exceeds the use requirements of high-frequency materials and is more suitable for circuit materials under high frequencies.

[0054] 2. This application modifies the filler and stipulates that the filler is porous and nano-grade. The porous material can fully absorb the modifier, improve the stability of the filler in the system and enhance the material performance. The nano-grade material fills the gaps between the porous fillers from the structural grading level, which can increase the density of the material and the protection of the circuit substrate, and better relieve the stress on the material to avoid film cracks caused by stress mismatch. The type and amount of the modifier are further specified, and the rigidity and toughness of the material are balanced by the intermolecular force between the modifier and the polymer, thereby improving its structural stability and reducing dielectric loss.

[0055] 3. Through system optimization, the conformal material of this application also exhibits excellent adhesion, density, salt spray resistance, moisture and heat resistance, and thermal shock resistance, and can be used on flexible circuit boards for 5G high-frequency technology. DETAILED DESCRIPTION

[0056] Example

[0057] Example 1

[0058] This embodiment provides a circuit board conformal coating material for high-frequency fields, wherein the raw materials of the material include: by weight, 45 parts of ethylene-vinyl acetate copolymer, 15 parts of polypropylene, 17 parts of polytetrafluoroethylene emulsion, 20 parts of silicon dioxide, 2 parts of antioxidant, and 1 part of flame retardant;

[0059] The VA content of the ethylene-vinyl acetate copolymer is 28%, the melt index is 25g / 10min (190℃ / 2.16kg), model: DuPont 250A; the number average molecular weight of the polypropylene is 5000, purchased from Maoming Petrochemical; the solid content of the polytetrafluoroethylene emulsion is 60%, purchased from Zhejiang Juhua, JF-4DCD; the silica is porous silica and nano-scale silica, the mass ratio of the two is 3:1, and the BET specific surface area of ​​the porous silica is 260m 2 / g, D50 particle size is 2μm, purchased from Oulite New Material Technology Co., Ltd., SDK-02; the average diameter of the nano-scale silicon dioxide particles is 20nm, purchased from Jiangsu Tianxing New Materials Co., Ltd., TSP-L12; the antioxidant is tri(tridecyl) phosphite and antioxidant 1010, the mass ratio is 1:5; the flame retardant is decabromodiphenyl ether;

[0060] The silicon dioxide is modified by styrene ethyl trimethoxy silane and 1,3-bis (3-aminopropyl) -1,1,3,3-tetramethyl disiloxane, and the modification method is: immersing the silicon dioxide in a 10wt% ethanol / water mixed solution (v / v is 1:1) of the modifier, heating the system to 100°C, stirring the reaction for 6 hours, filtering and drying; the modifier in the solution accounts for 55% of the mass of the silicon dioxide; the modifier is styrene ethyl trimethoxy silane and 1,3-bis (3-aminopropyl) -1,1,3,3-tetramethyl disiloxane, and the mass ratio of the two is 1:1;

[0061] The preparation method of the conformal coating material is as follows: the raw materials are put into a kneader, the heat transfer oil is heated to 180° C. using a mold temperature controller, and then vacuumed to negative pressure (-0.8 MPa, 0.5 h), stirring and mixing under negative pressure for 2 h, breaking the vacuum with N2 to restore normal pressure, and continuing stirring for 1 h; finally, the mixture is placed in a mold and cooled.

[0062] Example 2

[0063] This embodiment provides a circuit board conformal coating material for high-frequency fields, wherein the raw materials of the material include: by weight, 40 parts of ethylene-vinyl acetate copolymer, 10 parts of polypropylene, 30 parts of polytetrafluoroethylene emulsion, 18 parts of silicon dioxide, 1 part of antioxidant, and 1 part of flame retardant;

[0064] The VA content of the ethylene-vinyl acetate copolymer is 33%, the melt index is 30g / 10min (190℃ / 2.16kg), model: DuPont 150W; the number average molecular weight of the polypropylene is 4000, purchased from Maoming Petrochemical; the solid content of the polytetrafluoroethylene emulsion is 60%, purchased from Zhejiang Juhua, JF-4DCD; the silica is porous silica and nano-scale silica, the mass ratio of the two is 3:2, and the BET specific surface area of ​​the porous silica is 240m 2 / g, D50 particle size is 4μm, purchased from Oulite New Material Technology Co., Ltd., SDK-04; the average diameter of the nano-scale silicon dioxide particles is 20nm, purchased from Jiangsu Tianxing New Materials Co., Ltd., TSP-L15; the antioxidant is tri(tridecyl) phosphite and antioxidant 1010, the mass ratio is 1:4; the flame retardant is decabromodiphenyl ether;

[0065] The silicon dioxide is modified by styrene ethyl trimethoxy silane and 1,3-bis (3-aminopropyl) -1,1,3,3-tetramethyl disiloxane, and the modification method is: immersing the silicon dioxide in an ethanol / water mixed solution (v / v is 1:1) containing 8wt% of the modifier, heating the system to 90°C, stirring the reaction for 8h, filtering and drying; the modifier in the solution accounts for 50% of the mass of the silicon dioxide; the modifier is styrene ethyl trimethoxy silane and 1,3-bis (3-aminopropyl) -1,1,3,3-tetramethyl disiloxane, and the mass ratio of the two is 2:1;

[0066] The preparation method of the conformal coating material is as follows: the raw materials are put into a kneader, the heat transfer oil is heated to 170°C using a mold temperature controller, and then vacuumed to negative pressure (-0.8MPa, 0.5h), stirring and mixing under negative pressure for 2h, breaking the vacuum with N2 to restore normal pressure, and continuing stirring for 1h; finally, the mixture is loaded into a mold and cooled.

[0067] Example 3

[0068] This embodiment provides a circuit board conformal coating material for high-frequency fields, wherein the raw materials of the material include: by weight, 50 parts of ethylene-vinyl acetate copolymer, 20 parts of polypropylene, 15 parts of polytetrafluoroethylene, 25 parts of silicon dioxide, 3 parts of antioxidant, and 5 parts of flame retardant;

[0069] The VA content of the ethylene-vinyl acetate copolymer is 32%, the melt index is 43g / 10min (190℃ / 2.16kg), model: DuPont 3185; the number average molecular weight of the polypropylene is 8000, purchased from Maoming Petrochemical; the solid content of the polytetrafluoroethylene emulsion is 60%, purchased from Zhejiang Juhua, JF-4DCD; the silica is porous silica and nano-scale silica, the mass ratio of the two is 4:1, and the BET specific surface area of ​​the porous silica is 260m 2 / g, D50 particle size is 2μm, purchased from Oulite New Material Technology Co., Ltd., SDK-02; the average diameter of the nano-scale silicon dioxide particles is 20nm, purchased from Jiangsu Tianxing New Materials Co., Ltd., TSP-L30; the antioxidant is tri(tridecyl) phosphite and antioxidant 1010, the mass ratio is 1:6; the flame retardant is decabromodiphenyl ether;

[0070] The silicon dioxide is modified by styrene ethyl trimethoxy silane and 1,3-bis (3-aminopropyl) -1,1,3,3-tetramethyl disiloxane, and the modification method is: immersing the silicon dioxide in a 15wt% ethanol / water mixed solution (v / v is 1:1), heating the system to 105°C, stirring the reaction for 4h, filtering and drying; the modifier in the solution accounts for 70% of the mass of the silicon dioxide; the modifier is styrene ethyl trimethoxy silane and 1,3-bis (3-aminopropyl) -1,1,3,3-tetramethyl disiloxane, and the mass ratio of the two is 0.5:1;

[0071] The preparation method of the conformal coating material is as follows: the raw materials are put into a kneader, the heat transfer oil is heated to 200° C. using a mold temperature controller, and then vacuumed to negative pressure (-0.8 MPa, 0.5 h), stirring and mixing under negative pressure for 2 h, breaking the vacuum with N2 to restore normal pressure, and continuing stirring for 1 h; finally, the mixture is placed in a mold and cooled.

[0072] Comparative Example 1

[0073] The method is basically the same as Example 1, except that the VA content of the ethylene-vinyl acetate copolymer is 18%, the melt index is 30 g / 10 min (190° C. / 2.16 kg), and the model is DuPont 3176.

[0074] Comparative Example 2

[0075] The method is basically the same as Example 1, except that the filler is nano-scale silicon dioxide, and the average particle diameter is 20 nm.

[0076] Comparative Example 3

[0077] The method is basically the same as Example 1, except that the silicon dioxide is modified by styrene ethyl trimethoxy silane and 1,3-bis(3-aminopropyl)-1,1,3,3-tetramethyldisiloxane, and the mass ratio of styrene ethyl trimethoxy silane to 1,3-bis(3-aminopropyl)-1,1,3,3-tetramethyldisiloxane is 1:3.

[0078] Performance testing method:

[0079] 1. Dielectric properties: The dielectric constant D of the conformal coating material obtained in the embodiment is measured at a frequency of 10 GHz according to the IEC-61189-2-721 standard. k and loss factor D f Conduct a test.

[0080] 2. Adhesion: The adhesion strength of the conformal coating material of each embodiment was tested according to GB / T 9286-1998 standard.

[0081] 3. Salt spray test: The test is carried out in accordance with GB / T2423.17-2008 standard, the test conditions are 5% NaCl solution, the test time is 1000h, and the test is passed if there are no defects on the surface of the conformal coating material.

[0082] 4. Moisture test: Test according to IPC-TM-650 2.6.3.7 standard, test conditions are 90℃, 95%RH, time is 1000h, if there is no defect on the material surface, it means it has passed the test.

[0083] 5. Thermal shock test: The test is carried out in accordance with the IPC-TM-650 2.6.7.1 test standard. The test conditions are -40 ~ 125 ° C cycle test, -40 ° C stay for 15 minutes, 125 ° C stay for 15 minutes, the conversion time is 5 minutes, and the test is repeated for 500 cycles. If there are no defects on the surface of the conformal coating material, it means that the test has passed.

[0084] Performance test results:

[0085] Table 1

[0086]

Claims

1. A conformal coating material for circuit boards used in high frequency fields, characterized in that: The raw materials are: by weight, 45 parts of ethylene-vinyl acetate copolymer, 15 parts of polypropylene, 17 parts of polytetrafluoroethylene emulsion, 20 parts of silicon dioxide, 2 parts of antioxidant, and 1 part of flame retardant; The ethylene-vinyl acetate copolymer has a VA content of 28%, a melt index of 25 g / 10 min at 190° C. and 2.16 kg, and a model number of DuPont 250A; The number average molecular weight of the polypropylene is 5000, purchased from Maoming Petrochemical; The polytetrafluoroethylene emulsion has a solid content of 60% and is purchased from Zhejiang Juhua, JF-4DCD; The silicon dioxide is porous silicon dioxide and nano-silicon dioxide, and the mass ratio of the two is 3:1; the BET specific surface area of ​​the porous silicon dioxide is 260m 2 / g, D50 particle size is 2 μm; the average particle diameter of the nano-scale silicon dioxide is 20 nm; The antioxidant is tri(tridecyl) phosphite and antioxidant 1010, with a mass ratio of 1:5; The flame retardant is decabromodiphenyl ether; The silicon dioxide is modified by styrene ethyl trimethoxy silane and 1,3-bis(3-aminopropyl)-1,1,3,3-tetramethyldisiloxane, and the modification method is: immersing the silicon dioxide in an ethanol-water mixed solution with a volume ratio of 1:1 and 10wt% of the modifier, heating the system to 100°C, stirring the reaction for 6h, filtering and drying; the modifier in the solution accounts for 55% of the mass of the silicon dioxide; the modifier is styrene ethyl trimethoxy silane and 1,3-bis(3-aminopropyl)-1,1,3,3-tetramethyldisiloxane, and the mass ratio of the two is 1:

1.

2. The method for preparing a conformal coating material according to claim 1, characterized in that: The method comprises the following steps: putting the raw materials into a kneading machine, using a mold temperature controller to heat the heat transfer oil to 160-200°C, then evacuating to negative pressure, stirring and mixing for 2-3 hours, then returning to normal pressure, and continuing to stir for 0.5-1 hour; finally, putting the mixture into a mold and cooling it.

Citation Information

Patent Citations

  • Preparation method of copper-clad plate with low dielectric constant, low dielectric loss and low CTE

    CN113978061A

  • Non-woven fabric with low dielectric loss as well as preparation method and application of non-woven fabric

    CN115075057A

  • Hot-melt conformal coating material suitable for 5G high frequency field

    CN110628292A